To burn or not to burn: an approach to control waste in our society highlighting the Relationship between energy, recycling and communities - Kabongo, Benedictte (My University, 2024)
The capacity of South Africa and other developing countries is as minimal. On the other hand, the growing trends - population growth, industrialization, and economic growth- in modern-day society have improved human wellness. As a result, when resource consumption rises, so as solid waste. However, in developing countries, the generation of waste per capita is the lover compared to developed countries; the main challenge is the capacity to handle it effectively. Moreover, efficiently landfill, recycle and reuse. The resource consumption model in developing countries is linear, meaning that processing, producing, using, and discarding products to nature harms the environment through the emission of greenhouse gas, the pollution of land and water resource, and boost climate effect. In the last decade, solid waste management has improved technologically and operationally and responds to environmental concerns; its focus is on the end-stage solutions, focusing on the reduction of waste rather than sustainability, whose core focus is the prevention of waste. South Africa’s approach regarding solid waste is to push waste up towards minimal production, reuse, and recycling through comprehensive producer responsibility and economic instruments This research focuses on the factors impacting solid waste management in South Africa and will put forward realistic avenues for using solid waste as a resource. In addition, it will help find successful initiatives highlighting inclusive planning and management of those facilities. Finally, this finds approaches for the private sector, the government, and the community to link service and value chains in sustainable solid waste management. For example, it adopts practices that divert waste from landfills, formalizes reclaimers or waste pickers, initiates waste-to-energy technologies, and encourages recycling at all waste cycle stages.
A dissertation submitted in partial fulfilment of the requirements for the degree Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2021
Keywords: Solid waste management; Resource consumption